2019
DOI: 10.1101/825810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct roles for motor cortical and thalamic inputs to striatum during motor learning and execution

Abstract: The acquisition and execution of learned motor sequences are mediated by a distributed motor network, spanning cortical and subcortical brain areas. The sensorimotor striatum is an important cog in this network, yet how its two main inputs, from motor cortex and thalamus respectively, contribute to its role in motor learning and execution remains largely unknown. To address this, we trained rats in a task that produces highly stereotyped and idiosyncratic motor sequences. We found that motor cortical input to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 174 publications
(294 reference statements)
3
12
0
Order By: Relevance
“…In one of the aforementioned time-estimation studies, a lesion of the primary motor cortex in naive rats prevented the learning of the embodied strategy but the same lesion was without effect when performed after learning. It was suggested that, during learning, the motor cortex provided a 'tutor' signal to subcorticals motor regions [60], most likely to the DLS [61]. In our general hypothesis, efference copy of motor programs and somatosensory responses would tutor DS SPN.…”
Section: A Role For Striatal Somatosensory Responses In Motor Learningmentioning
confidence: 66%
“…In one of the aforementioned time-estimation studies, a lesion of the primary motor cortex in naive rats prevented the learning of the embodied strategy but the same lesion was without effect when performed after learning. It was suggested that, during learning, the motor cortex provided a 'tutor' signal to subcorticals motor regions [60], most likely to the DLS [61]. In our general hypothesis, efference copy of motor programs and somatosensory responses would tutor DS SPN.…”
Section: A Role For Striatal Somatosensory Responses In Motor Learningmentioning
confidence: 66%
“…As we found that cholinergic inputs to both mPFC and motor cortex are required for coordinated motor acquisition, it is likely that cholinergic neuromodulation plays a critical role in the coactivation of mPFC-DMS and M1-DLS circuits during early stage rotarod learning (Kupferschmidt et al, 2017). As training progresses and instructional input from cortical projections is no longer driving experience-dependent refinement of striatal motor circuits (Wolff et al, 2019), cholinergic neuromodulation of cortical motor centers is no longer required. This is supported by our findings that ablation of cholinergic neurons after rotarod training elicited no effect on performance of the previously trained task.…”
Section: Discussionmentioning
confidence: 79%
“…We shall show below that this is indeed the case. After developing the theory for this two-pathway model, we shall show in the following section that identifying the second input to striatum as thalamus provides an explanation for the asymmetric effects of motor cortical and thalamic lesions in rats described in the "Introduction" [28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…In the case h = 0, on the other hand, the repeated pattern was not recalled accurately, illustrating that the input from the second pathway is necessary to protect practiced patterns from being overwritten. Thus, interpreting the two input pathways as cortical and thalamic inputs to striatum, the model accounts for the experimental observations in rodents that skilled behaviors and neural representations of kinematic variables are robust to the loss of cortical inputs [29][30][31] , but that such behaviors are not robust to the loss of thalamic input 28 . In summary, when an input pathway with fast supervised learning and another with slow Hebbian learning together drive a downstream population, the mechanisms of input alignment and control transfer enable the second input to gradually take over the role of the first in driving the downstream activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation